Composition, Chemical Variability and Biological Activity of Cymbopogon schoenanthus Essential Oil from Central Algeria. Issue 6 (13th May 2020) - Malti, Charaf Eddine Watheq; El Haci, Imad Abdelhamid; Hassani, Faiçal; Paoli, Mathieu; Gibernau, Marc; Tomi, Félix; Casanova, Joseph; Bekhechi, Chahrazed
Abstract: Cymbopogon schoenanthus (L.) Spreng . (Poaceae) is an aromatic plant whose aerial parts and rhizome produced an essential oil with pleasant odor. A chemical variability has been observed depending of the countries where the plant grows wild, including Algeria. The chemical compositions of 24 oil samples isolated from plants harvested in Central Algeria have been investigated, to evidence homogeneity or chemical variability within a given area of harvest. Twenty of these were dominated by cis ‐ and trans ‐ p ‐menth‐2‐en‐1‐ols (22.6 %±3.6 and 14.3 %±1.7, resp.) beside four atypical compositions. Otherwise, aerial parts and rhizomes produced similar essential oils. Lastly, a fair antimicrobial activity was measured against Staphylococcus aureus strain, while the antioxidant potential was low. Abstract :